Analisis Profitabilitas Terhadap Bank Syariah Indonesia (BSI) Sebelum Dan Setelah Merger - Yumiza Aprilia Putri; Kartika Malika Putri; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
The merger of Islamic Banks is to encourage larger Islamic banks to participate in the global market and to become a catalyst for Islamic economic growth in Indonesia. In addition, the merger of Islamic banks is considered more efficient in raising funds, operations and spending. Therefore, this study aims to determine the financial performance of Bank Syariah Indonesia before and after the merger. The object of this study is the financial statements of Bank Syariah Indonesia for 2018 – 2021. The method used is descriptive quantitative with the aim of analyzing BSI profitability before and after the merger. The types of data used are primary and secondary data obtained from several journals and the official website of the Indonesia Stock Exchange and the official website of Bank Syariah Indonesia (BSI). The results showed that there was no increase that was too specific between before and after the merger was carried out, where each company had its own operational and non-operational costs if the merger was not automatically carried out, so looking at the assets owned by each company, it can be said that the merger should be done. At the time the merger was carried out because the costs incurred by the company from all costs due to the implementation of the merger were more profitable than before the merger.